Policy analysis: User monitoring of in-vitro diagnostic medical devices used for near-patient testing of infectious diseases. Issue 1 (2nd August 2022) - Dimech, Wayne; Sands, Anita; Lamoury, Francois; Ding, Xavier C; Lastra, Leticia Megias
Abstract: Background: All individuals should have equitable access to accurate and timely testing for infectious diseases, which underpins diagnosis and treatment, safeguards blood supplies, and is used to determine disease prevalence. Disadvantaged populations have limited access to laboratory-based testing, so near-patient or point-of-care testing (PoCT) has been developed and implemented. Unlike laboratory-based testing, PoCT is often performed by non-laboratory staff and outside regulatory frameworks. Quality assurance (QA) of PoCT is often lacking or inappropriate, meaning inaccurate testing can go undetected, leading to poor patient outcomes. Objective: To review the application of QA of PoCT use to detect infectious diseases and propose fit-for-purpose alternatives. Method: A review of the current QA of PoCT was undertaken by experienced QA providers by mapping the points of failure. Barriers to providing PoCT QA include inappropriate and unstable sample types; expensive shipping to remote sites, including dry ice shipment; cost of international QA programmes; regulatory costs; fixed test events; and a lack of technology for simple, centralized data collection facilitating rapid analysis and reporting of test results. Based on these findings, a novel, fit-for-purpose model of QA for PoCT for infectious diseases is described. Results: The new model for QA for PoCT identifies and describes novel sample types, including dry tube samples, dried swabs, or liquid-stable clinical samples that are inactivated and stable at ambient temperature; modified distribution channels; and a method for data collection and analysis using mobile phone technology. Conclusion: The findings of this paper seek to describe a fit-for-purpose process, which aims to improve the quality of testing for infectious diseases at PoCT, globally.